Finite element analysis of the plastic deformation in tandem process of simple shear extrusion and twist extrusion. (15th October 2015) - Kim, Jung Gi; Latypov, Marat; Pardis, Nima; Beygelzimer, Yan E.; Kim, Hyoung Seop
Graphical abstract: Highlights: A tandem process of the simple shear extrusion and twist extrusion was proposed. Deformation heterogeneity was investigated using the finite element method. The tandem process produces more homogeneous and larger deformation than extrusion. Abstract: Recently, simple shear extrusion (SSE) and twist extrusion (TE) are introduced to fabricate ultrafine grained bulk rod metallic materials. The SSE and TE processes generate significant deformation inhomogeneity, with higher and lower strains in the center, respectively, which easily causes mechanical instability of the materials. In this study, to overcome this deformation inhomogeneity problem in SSE and TE, a tandem process of SSE and TE (TST) is suggested. The finite element method is applied for plastic deformation behavior during the TST process. The results demonstrate that the TST process can produce relatively homogeneously deformed materials. In particular, the effects of back pressure and processing order on the plastic deformation behaviors in the TST process are systematically analyzed.